IMPLEMENTATION OF ARTICLE 8 LAMPUNG PROVINCIAL DPRD REGULATION NUMBER 1 OF 2019 REGARDING PROCEDURE FOR DETERMINING THE MAXIMUM NUMBER OF DRAFT REGIONAL REGULATIONS - Indah Satria; Sunarsih Sunarsih (PRANATA HUKUM, 2023)
Propemperda is a planning instrument for the formation of regional regulations which are arranged in a planned, integrated and systematic manner. Article 8 paragraph (5) Regulation of the DPRD Province of Lampung Province 1/2019, the determination of Propemperda takes into account the realization of Propemperda with local regulations which are stipulated every year with a maximum addition of 25% of the number of regional regulations stipulated in the previous year. In 2020 the Province of Lampung established 5 regional regulations, so the Propemperda for 2021 should have 7 regional regulations but instead stipulated 25 regional regulations. This stipulation has an impact on the quality of regional legal products produced, the existence of regional regulations that have been canceled and the low IDI of the Lampung Provincial Government in the field of law and the formation of regional legal products. Article 8 paragraph (5) DPRD Regulation 1/2019 has been implemented but has not been maximized due to obstacles. The obstacles include not having gone through the Regional Regulation Needs Analysis and the absence of a regional regulation on Procedures for Forming Propemperda. The implication of the ranperda which exceeds the stipulated amount is the low IDI value for Lampung Province.